Tekstil tenunan Melayu : keindahan budaya tradisional Nusantara - Siti Zainon Ismail, 1949- (Kuala Lumpur: Dewan Bahasa dan Pustaka, Kementerian Pendidikan, Malaysia, 1994)
Malaysian tradisional hand made textile.
In Malay.
Includes bibliographical references (p. 98-99) and index.
Keywords: Textile design -- Malaysia; Textile fabrics -- Malaysia